A new species of Allobates (Anura: Aromobatidae) from Parque Nacional da Amazônia, Pará State, Brazil - Lima, Albertina P.; Simões, Pedro Ivo; Kaefer, Igor Luis (Zootaxa, 2015)
We describe the fourth species of nurse-frog genus Allobates occurring in the southeastern Brazilian Amazonia. The new species is sympatric with Allobates femoralis, Allobates masniger and Allobates magnussoni, and inhabits the margins of streams in forested areas within Parque Nacional da Amazônia, on the western bank of the Tapajós River. Snout-to-vent length ranges between 14.9–16.1 mm among males and 15.6–16.5 mm among females. The species is distinguished by the light brown background color of dorsum, with irregular dark brown blotches appearing from eye level to the urostyle region. In life, ventral surfaces of males are golden yellow on throat and chest, and white to yellow on abdomen. Ventral surfaces of females are predominantly white, except for light yellow on chin. The dark brown lateral band has a diffuse lower edge ventrolaterally. Dorsal surface of thigh is cream, with a longitudinal dark brown band extending dorsally from vent to knee. Tail musculature of tadpoles is robust, bifurcating dorsally over the body and reaching about two-thirds of the body length. Advertisement calls consist predominantly of continuous pairs of notes, but other note arrangements are also emitted. Notes have ascending frequency modulation and average peak frequency ranging between 5.3–5.9 kHz. First and second notes of the same note pair are similar in amplitude, duration and frequency spectrum. Successive note pairs are split by approximately regular silent intervals (0.30–0.49 s). The species lays its eggs inside rolled or folded dead leaves on the leaf litter. Egg capsules and jelly nests are opaque.